Religious Tolerance Messages on Social Media: Insights from Deddy Corbuzier's 'Log in' Program - Muh Ali Bagas; Heriyadi; Firyal, Wafda (Al'Adalah, 2024)
The rise of social media has intensified challenges related to misinformation and interfaith conflicts, underscoring the critical need for platforms promoting religious tolerance. This study investigates the "Log in" program on Deddy Corbuzier's YouTube channel, which uniquely employs interactive interfaith dialogue to foster understanding in Indonesia's pluralistic society. Previous studies emphasized the role of static social media content in advancing tolerance, leaving gaps in examining dynamic, dialogue-driven approaches. This research identifies messages of tolerance categorized into faith, sharia, and morals, demonstrating the flexibility and inclusivity necessary for harmonious interfaith relations. The study used qualitative descriptive methods and narrative content analysis to analyze ten representative videos featuring religious leaders from diverse traditions. The findings highlight the program's novelty in using humor and dialogue to bridge religious divides, effectively conveying tolerance messages to diverse audiences. Despite the program's success, challenges persist, such as combating hate speech and measuring the impact on societal attitudes. Recommendations include broader digital platform studies and policy support for moderating intolerance online. The study contributes to academic discourse on digital interfaith engagement, offering insights into leveraging social media for global harmony amidst cultural and religious diversity.